Sistem Ngadas Sapi Persepektif Hukum Ekonomi Syariah Dan Hukum Adat (Studi Kasus Di Desa Mekarsari Kecamatan Gunungsari) - MUh. Zidni Syukran; Abrar (TAFAQQUH, 2024)
This research aims to address the following questions: (1) How is the implementation of the "ngadas sapi" system in Mekarsari Village, Gunungsari District conducted, and (2) What are the perspectives of sharia economic law and customary law on the "ngadas sapi" system in Mekarsari Village, Gunungsari District. This study is qualitative research, specifically a field research. The approach used is descriptie qualitative, analyzing data based on interview results. Data collection techniques include direct observation in Mekarsari Village, interviews to support and complement the research information, and documentation to supplement data and theory. The results of the study indicate that the cooperation in the form of "ngadas sapi" in Mekarsari Village is a type of business activity that falls under the wage contract category. According to customary law, it has become a legal basis as it has been established as a local custom and does not contradict other laws